Oncotargeting by Vesicular Stomatitis Virus (VSV): Advances in Cancer Therapy - Bishnoi, Suman (Viruses, 2018)
Modern oncotherapy approaches are based on inducing controlled apoptosis in tumor cells. Although a number of apoptosis-induction approaches are available, site-specific delivery of therapeutic agents still remain the biggest hurdle in achieving the desired cancer treatment benefit. Additionally, systemic treatment-induced toxicity remains a major limiting factor in chemotherapy. To specifically address drug-accessibility and chemotherapy side effects, oncolytic virotherapy (OV) has emerged as a novel cancer treatment alternative. In OV, recombinant viruses with higher replication capacity and stronger lytic properties are being considered for tumor cell-targeting and subsequent cell lysing. Successful application of OVs lies in achieving strict tumor-specific tropism called oncotropism, which is contingent upon the biophysical interactions of tumor cell surface receptors with viral receptors and subsequent replication of oncolytic viruses in cancer cells. In this direction, few viral vector platforms have been developed and some of these have entered pre-clinical/clinical trials. Among these, the Vesicular stomatitis virus (VSV)-based platform shows high promise, as it is not pathogenic to humans. Further, modern molecular biology techniques such as reverse genetics tools have favorably advanced this field by creating efficient recombinant VSVs for OV; some have entered into clinical trials. In this review, we discuss the current status of VSV based oncotherapy, challenges, and future perspectives regarding its therapeutic applications in the cancer treatment.